NATIONALISM AND GLOBALIZATION: ISSUES ON THE SEA BORDER BEETWEN INDONESIA AND AUSTRALIA IN THE CONTEXT OF MARITIME SOVEREIGNTY - Zuhdi, Susanto; Sari, Noor Fatia Lastika; Sunarti, Linda (UI Scholars Hub, 2019)
This paper analyzes transnationalism as the result of globalization in human mobility, which it has summoned new insecurities, especially when international migration as the excess of transnationalism leads to a burst of issues on the sea border, such as influx of migration, asylum seeker, refugees, and even transnational crimes. Thus, it is very important for Indonesia as a growing maritime state to put more attention to the matter, especially to the eastern part of the archipelago, where transnationalism brings different implication toward nationalism of its people. Through historical methodology and perspective, this article discusses relevant issues to be reflected into current situation and the future, in which it could lead to a more sustainable solution and a further observation toward what it means to be a part of Indonesia itself, to fulfill the need of rephrasing the means of our borders.